2003
DOI: 10.1074/jbc.m201264200
|View full text |Cite
|
Sign up to set email alerts
|

Regional Loss of the Mitochondrial Membrane Potential in the Hepatocyte Is Rapidly Followed by Externalization of Phosphatidylserines at That Specific Site during Apoptosis

Abstract: The spatio-temporal relationship between a decrease in the mitochondrial membrane potential (MMP) and externalization of phosphatidylserines (PS) during induction of apoptosis was investigated in single freshly isolated hepatocytes. Apoptosis was induced in the hepatocytes in three different ways: attack by activated Natural Killer cells, exposure to ATP, or exposure to the inhibitor of protein synthesis cycloheximide. Fluorescence microscopy showed staining of externalized PS at those areas where the staining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 40 publications
(23 reference statements)
0
29
0
Order By: Relevance
“…Depolarization of the mitochondrial membrane potential can enhance the release of apoptotic factors from mitochondria to the cytoplasm and induce cell apoptosis. 13,14 Pretreatment of NO completely ameliorated the oxidative stress-caused decreases in the mitochondrial membrane potential. Thus, recovery of the mitochondrial membrane potential is an important reason explaining NO's protection against oxidative stress-induced osteoblast apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depolarization of the mitochondrial membrane potential can enhance the release of apoptotic factors from mitochondria to the cytoplasm and induce cell apoptosis. 13,14 Pretreatment of NO completely ameliorated the oxidative stress-caused decreases in the mitochondrial membrane potential. Thus, recovery of the mitochondrial membrane potential is an important reason explaining NO's protection against oxidative stress-induced osteoblast apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in the synthesis or translocation of the proapoptotic Bax protein can trigger depolarization of the mitochondrial membrane potential, enhancing the release of apoptotic factors such as cytochrome c, and ultimately leading to cell apoptosis. [13][14][15] Being an effector for death regulation, NO has been shown to decrease bone mineral density through induction of osteoblast apoptosis in inflammationinduced osteoporosis. 16 Our previous studies showed that NO can activate mitochondrial apoptotic signals that induce osteoblast apoptosis.…”
Section: Introductionmentioning
confidence: 99%
“…The apoptotic process involves a series of biochemical steps and structural changes including mitochondrial membrane potential (MMP) depolarization, chromatin condensation, nuclear fragmentation, cytoskeletal reorganization, cell shrinkage, and membrane blebbing [3,16]. Caspases have been implicated as mediators of apoptosis in a variety of mammalian cell types [11,18].…”
Section: Introductionmentioning
confidence: 99%
“…Intracellular ATP levels participate in regulation of cell apoptosis and necrosis. 23,37 Therefore, NO may decrease cellular ATP levels through suppression of the mitochondrial membrane potential and complex I enzyme activity in human chondrocytes and induces cell insults.…”
mentioning
confidence: 99%
“…16,22 Increases in the synthesis or translocation of Bax, a proapoptotic protein, can trigger depolarization of the mitochondrial membrane potential, enhancing the release of cytochrome c, and ultimately leading to cell apoptosis. 23 Phosphorylation of MAPKs by MEKK1 has been reported to activate the Bax-caspase protease pathway and plays a pivotal role in high glucose-induced apoptosis of human endothelial cells. 24 However, the roles of the cytoskeleton and MEKK1/JNK in NO-induced insults to chondrocytes need to be evaluated.…”
mentioning
confidence: 99%